Walnuts, Long-Chain Polyunsaturated Fatty Acids, and Adolescent Brain Development: Protocol for the Walnuts Smart Snack Dietary Intervention Trial - Julvez, Jordi; Gignac, Florence; Fernández-Barrés, Silvia; Romaguera, Dora; Sala-Vila, Aleix; Ranzani, Otavio T.; Persavento, Cecilia; Delgado, Anna; Carol, Albert; Torrent, Jaume; Gonzalez, Judith; Roso, Eduard; et al. (Frontiers in Pediatrics, 2021)
Background: Adolescence, when the most complex behaviors are refined to adulthood sophistication, represents a major window of opportunity and vulnerability for neuropsychological development. To support and protect this complex and active brain’s growth, different nutritional components qualified as essential need to be acquired from the diet. For instance, omega-3 fatty acids are mainly obtained from seafood, seeds and walnuts. Known for their rich lipid profile, walnuts contain sizable amounts of an essential fatty acid, alpha-linolenic acid (ALA), the vegetable omega-3 fatty acid that is the precursor of two longer-chain omega-3 polyunsaturated fatty acids (omega-3 PUFA): docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids. While there is accruing evidence on neuropsychological improvements in the young developing brain associated with omega-3 PUFA intake, few studies have examined whether consuming walnuts during adolescence entails similar beneficial effects. There is a need to further explore the ways in which walnuts influence youth brain function, particularly on the long-term. Thus, we designed the WALNUTs study (WSS), a population-based randomized controlled trial conducted in adolescents in Barcelona, Spain. We hypothesize that walnut intake will increase omega-3 PUFA tissue availability (particularly ALA) to a level that enhances the neuropsychological development during adolescence. Methodology/Design: We conducted a 6-month population-based randomized controlled trial in teenagers (n=800) and we aimed to determine the effectiveness of the intervention (four walnuts per day, or 30 kernel g, ~1.5g of ALA) in enhancing brain neuropsychological and socio-emotional development compared to a control group with no walnut intervention. Before randomization, different neuropsychological tests were recorded for all participants, and blood samples (in a subsample of participants) were collected to measure omega-3 PUFA levels at baseline, and all again, after randomization and the intervention. The data is now collected and we will conduct linear regression models to assess the effect of the intervention. Discussion: The WALNUTs (WSS) study results will allow us to better understand the role of plant-based omega-3 PUFA intake from regular walnut consumption on neuropsychological development during adolescence. Results could be translated into nutritional public health recommendations targeting teenagers.